Analysis of Offensive Patterns After Timeouts in Critical Moments in the EuroLeague 2022/23 - Christopher Vázquez-Estévez; Iván Prieto-Lage; Xoana Reguera-López-de-la-Osa; Antonio José Silva-Pinto; Juan Carlos Argibay-González; Alfonso Gutiérrez-Santiago (Applied Sciences)
Timeouts are a widely supported strategy in the literature, recognized for directly influencing team performance during basketball games. This study aimed to analyze and define the successful patterns of actions after timeouts (ATOs) during critical moments in the 2022/23 EuroLeague season. The sample was drawn from the last two minutes and overtime of 169 games with a final point difference of 10 points or fewer, totaling 365 ATOs. An observational methodology was used, applying the LINCE PLUS software version 2.1.0 and an ad hoc observational instrument. Descriptive analysis and chi-square tests (χ2) were conducted using SPSS 25.0, and T-pattern analysis was performed with Theme 6 software. Statistical significance was set at p < 0.05. Teams in the lead often concluded successful plays through free throws following opponent fouls, while teams trailing behind attempted to close the gap by committing fouls to force free throws in defense and scoring two-point baskets on offense. The findings offer insights into ATOs strategies that can support coaches and technical staff in training and adapting these actions to meet competition demands during critical game moments. These results may assist in enhancing team performance and decision-making under high-stakes conditions.